GOUT AND NONALCOHOLIC FATTY LIVER DISEASE: EFFECT OF ENTEROSORPTION’S ADDITION TO COMMON TREATMENT - Mudra, U. O. (International Journal of Medicine and Medical Research, 2020)
Background. Gout is still one of the major health problems despite significant advances in treatment in recent years. It has been proved that pathogenetic mechanisms of development and progression of gout are associated with nonalcoholic fatty liver disease. Complex pathogenic treatment of patients aimed at different parts of the pathological process has recently been supplemented with the enterosorbents. Objective. The aim of the research is to study the clinical features of gout with concomitant nonalcoholic fatty liver disease (NAFLD) and to evaluate the effect of carbon enterosorbent on its course. Methods. 123 patients were involved in the study. They were divided into 2 groups: group 1 included patients with gout without liver damage, and group 2 included patients with concomitant NAFLD. Each of these groups was divided into subgroups, in which the patients received carbon enterosorbent carboline plus basic treatment. The control group consisted of 30 healthy persons. Anamnesis, physical examination, uric acid (UA), C-reactive protein (CRP) content, erythrocyte sedimentation rate (ESR) in serum were determined. Gout activity was evaluated using the Gout Activity Score (GAS). Results. Basic treatment in combination with carbon enterosorbent contributed to faster cure of intoxication, pain and joint syndromes, as well as decrease of the inflammatory process activity. Conclusions. The course of gout in the patients with concomitant NAFLD is more severe. Adding of carbon granular enterosorbent carboline in the complex treatment of patients with gout with or without concomitant NAFLD in the exacerbation phase contributes to a faster cureing dynamics of clinical and laboratory manifestations of the disease.